Dampak Terorisme dan Peran Media Dalam Propaganda Islamofobia: Tinjauan Pustaka Sistematis - Muhammad Firdaus Syadzili (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
Terrorist movements have often been heard, both in Indonesia and in other remote parts of the country. Several studies have discussed whether terrorism is included in the impact of globalization where the movement spreads rapidly along with globalization and becomes one form of transnational movement that eventually enters other countries and develops rapidly and immediately spreads ideas to existing countries. First, identify the article. Articles are taken from publications by various authors using the Scopus database. The next step is to enter the keyword "ISLAMIC TERRORISM" in the publish column and provide a discussion of the year of publication only in the last few years, namely from 2018 to 2021. The media has an important role in acts of terrorism, both in spreading networks and acts of terror. Cyberterrorism is everywhere, more flexible than traditional terrorism, and most cyber attacks occur in the country of origin. Thus discussing the complex features of cyberterror networks and identifying some of their geostrategic implications of cyber strategy. The public should be able to sort out the information obtained to the stage of proving who the terrorist networks are involved in the acts of terror. It is hoped that people will consume information wisely and not be carried away by propaganda that could endanger themselves, their families and society.